Jules Joseph Dejerine: an outstanding neurologist and Charcot's enemy - Kondo, Gustavo Koíti; Schramm, Carla Caroline; Novaes, Max Rainer Rosado; Teive, Hélio Afonso Ghizoni (Arquivos de Neuro-Psiquiatria, 2018)
Jules Joseph Dejerine (1849-1917) became renowned for his many contributions to neurology, including his anatomical and anatomo-functional studies, particularly those in the field of language and the peripheral nervous system. A disciple of Vulpian and a rival of Charcot, Dejerine progressed rapidly in the academic world, reaching the peak of his career in 1911, when he was appointed to the chair of Nervous System Diseases at the Salpêtrière Hospital after defeating Pierre Marie (1853-1940), one of the most distinguished pupils of Jean-Martin Charcot (1825-1893).
Keywords: neurology; history; language; central nervous system; peripheral nervous system